ANALISIS YURIDIS TENTANG PENANAMAN MODAL ASING DARI PERSPEKTIF UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Melisarah Fernandez; I Made Sudirga (Jurnal Hukum Mahasiswa, 2026)
Foreign Direct Investment (FDI) plays a crucial role in driving national economic growth, technology transfer, and job creation in Indonesia. However, the practice of FDI in Indonesia still presents various legal challenges, particularly regarding the determination of minimum capital limits and the potential for regulatory abuse by foreign investors. This study examines the regulation of FDI under Law Number 25 of 2007 concerning Investment and the Investment Coordinating Board (BKPM) Regulation Number 4 of 2021. The method used is normative legal research with a statute approach and a conceptual approach. The findings show that the absence of explicit provisions on minimum capital in Law Number 25 of 2007 creates a legal vacuum that opens opportunities for manipulative practices, including nominee ownership schemes. Meanwhile, BKPM Regulation Number 4 of 2021 has set a minimum investment value of IDR 10,000,000,000, but remains weak in terms of verification and supervision of capital substance. This condition gives rise to the phenomenon of pseudo-FDI, which is administratively legitimate yet substantively hollow, thereby generating legal uncertainty, undermining the principle of justice, and threatening national economic sovereignty. This study concludes that regulatory harmonization, consistent law enforcement, and a strengthened supervisory role for authorized officials are essential to creating a fair, transparent, and legally certain investment system